Angular and polarization observables for Majorana-mediated B decays with effective interactions - Lucía Duarte; Gabriel Zapata; Oscar A. Sampayo (European Physical Journal C: Particles and Fields, 2020)
Abstract We probe the effective field theory extending the Standard Model with a sterile neutrino in B meson decays at B factories and lepton colliders, using angular and polarization observables. We put bounds on different effective operators characterized by their distinct Dirac–Lorentz structure, and probe the N-mediated B decays sensitivity to these interactions. We define a forward–backward asymmetry $$A_FB^{\ell γ }$$ A FB ℓ γ between the muon and photon directions for the $$B → μ ν γ $$ B → μ ν γ decay, which allows us to separate the SM contribution from the effective lepton number conserving and violating processes, mediated by a near on-shell N. Using the most stringent constraints on the effective parameter space from Belle and BaBar we find that a measurement of the final polarization $$P_{τ }$$ P τ in the rare $$B^-→ \ell ^-_{1}\ell ^-_{2} π ^+$$ B - → ℓ 1 - ℓ 2 - π + decays can help us infer the scalar or vector interaction content in the N production or decay vertices. We find that the B meson decays are more sensitive to scalar operators.